Trust in Management and Performance: Who Minds the Shop While the Employees Watch the Boss? - Mayer, Roger C.; Gavin, Mark B. (Academy of Management Journal, 2005)
This study investigated the relationships of the in-role performance and organizational citizenship behavior (OCB) of the employees in an organization with their trust in their plant managers and top management team. The study indicated that trust in these two managerial referents related to employees' ability to focus attention on value-producing activities and that this focus related to OCB.